Performance Appraisal Practices and Employee Engagement towards Academic Staff Performance in Higher Education Institution - Akanmu, Muslim Diekola; Duh, Helen (Journal of Cultural Analysis and Social Change, 2026)
The main objective of this study is to determine whether performance appraisal practices (PAPs) such as training, job promotion, financial reward, performance feedback, and performance recognition may be used as predictors of employee engagement and performance. A stratified sample approach was employed to collect responses from 203 academic employees of Malaysia Higher Education Institutions (HEIs) while the PLS-SEM was employed as a technique tool for reporting, data analysis, and hypothesis testing. The results show that while performance feedbacks, job promotions, and performance recognition have no significant impact on employee engagement, training and financial rewards have a significant and beneficial impact. However, the findings indicate that, with the exception of financial reward, there is a strong and favourable correlation between all PAPs and the employee performance. Employee performance is also significantly impacted by employee engagement. This finding implies that employee performance and engagement in academic contexts differ. The study reveals the reasons why policymakers and decision-makers in Malaysia’s education sector should concentrate more on how to maximize job promotions, performance feedbacks, and performance recognition for academic staff members at tertiary institutions and, on the other hand, financial rewards for efficient employee performance.